microRNA-214-3p Suppresses Ankylosing Spondylitis Fibroblast Osteogenesis via BMP–TGFβ Axis and BMP2 - Ding, Lixiang; Yin, Yukun; Hou, Yu; Jiang, Haoran; Zhang, Ji; Dai, Zhong; Zhang, Genai (Frontiers in Endocrinology, 2021)
Recent investigations suggest microRNAs (miRs) exert functions in fibroblast osteogenesis in ankylosing spondylitis (AS), an inflammatory rheumatic disease. But the mechanism of miR-214-3p in osteogenic differentiation in AS is not clearly understood yet. In this study, fibroblasts were obtained from the capsular ligament of patients with AS and femoral neck fracture, and cultured for osteogenic induction and identified. The roles of miR-214-3p and bone morphogenic protein 2 (BMP2) in AS fibroblast osteogenesis were assessed via gain-and loss-of function, alizarin red S staining and alkaline phosphatase (ALP) detection. Levels of miR-214-3p, BMP2, osteogenic differentiation-related proteins and BMP-TGFβ axis-related proteins were further measured. Consequently, miR-214-3p was downregulated in AS fibroblasts, with enhanced ALP activity and calcium nodules, which were reversed by miR-214-3p overexpression. BMP2 was a target gene of miR-214-3p, and promoted AS fibroblast osteogenesis by activating BMP-TGFβ axis, while miR-214-3p inhibited AS fibroblast osteogenesis by targeting BMP2. Together, miR-214-3p could prevent AS fibroblast osteogenic differentiation by targeting BMP2 and blocking BMP-TGFβ axis. This study may offer novel insight for AS treatment.